STRATEGI GURU DALAM MENGINTEGRASIKAN NILAI-NILAI ISLAMI PADA PEMBELAJARAN MATEMATIKA DAN IMPLIKASINYA TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS II SEKOLAH DASAR - Nur Safrina; Andi Wahdania AM; Nurjannah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers’ strategies in integrating Islamic values into mathematics learning and their implications for the character development of second-grade students at SDIT Qudwatun Hasanah Sinjai. This research employed a qualitative approach with a case study design. The research subjects were selected using purposive sampling, with the primary informant being a second-grade mathematics teacher. The study was conducted from March to April 2026. Data collection techniques included in-depth interviews, participant observation, and documentation. Data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and interactive conclusion drawing. The validity of the data was ensured through triangulation of sources, techniques, and time. The results indicate that teachers’ strategies in integrating Islamic values into mathematics learning are implemented through several approaches, namely linking mathematical concepts with Islamic teachings, habituation of prayer and learning etiquette, the use of contextual problems with Islamic values, the application of cooperative learning methods, and teacher role modeling as reinforcement of character values. These strategies are implemented in a planned, systematic, and continuous manner, both in classroom learning activities and in the school culture. The implications of these strategies are reflected in the development of students’ character, including the formation of religious character, increased honesty, discipline, responsibility, social skills, and learning motivation. Although there are challenges in aligning mathematical content with Qur’anic verses and limitations in learning media, school support plays an important role in the successful implementation. Therefore, the integration of Islamic values in mathematics learning not only strengthens cognitive aspects but also contributes significantly to students’ character development from an early age and can serve as a value-based learning model in integrated Islamic elementary schools.